2006
DOI: 10.1007/s00705-006-0825-9
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of infectious salmon anaemia virus (ISAV) in farmed populations of Atlantic salmon (Salmo salar)

Abstract: In the present study, 24 smolt production sites were screened for the presence of infectious salmon anaemia virus (ISAV) with the help of a specific real-time RT PCR assay, and 22 of these sites had smolts that were positive. If these smolt production sites are representative for the prevalence of ISAV in Norwegian smolts, then most marine production sites must be considered to be positive for ISAV. In addition, 92 European ISAV isolates have been genotyped based on the hemagglutinin-esterase gene (HE), and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
120
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(125 citation statements)
references
References 91 publications
(196 reference statements)
4
120
0
1
Order By: Relevance
“…The shift in virulence from ISAV-HPR0 to a disease-causing ISAV has been suggested to be a stochastic event dependent on the replication rate of the virus and the time available for virulence mutations to occur and accumulate [21]. Studies in fish and mammals have demonstrated that stress can play a key role in facilitating an increased viral replication rate because of a weakened immune response [54,55].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The shift in virulence from ISAV-HPR0 to a disease-causing ISAV has been suggested to be a stochastic event dependent on the replication rate of the virus and the time available for virulence mutations to occur and accumulate [21]. Studies in fish and mammals have demonstrated that stress can play a key role in facilitating an increased viral replication rate because of a weakened immune response [54,55].…”
Section: Discussionmentioning
confidence: 99%
“…The ORF of the HE gene of the 11 ISAV-HPR0 variants (see below) was sequenced and aligned with other publicly available sequences of the same segment [19,21,[32][33][34][35] using CLUSTAL X [63]. Identical sequences were identified with only a single representative type retained in the dataset to reduce subsequent analytical bias.…”
Section: Molecular Phylogenetic Analysis Of the He Genementioning
confidence: 99%
See 1 more Smart Citation
“…comm. ), while the 1998-1999 virus was of genogroup 3 (Nylund et al 2007) and mortality took longer to occur in salmon experimentally challenged with the 2008 virus (K. Urquhart unpubl. data).…”
Section: Origins Of the Outbreakmentioning
confidence: 99%
“…(Nylund et al 1993) and high levels of sea lice infestation have been suggested with major severity of ISA outbreaks in an expert-opinion based study (Gustafson et al 2005). Although vertical transmission has been suggested (Nylund et al 2007), there is little evidence of transmission via gonadal products.…”
Section: Introductionmentioning
confidence: 99%